2020
DOI: 10.1097/fpc.0000000000000406
|View full text |Cite
|
Sign up to set email alerts
|

Use of antidepressants with pharmacogenetic prescribing guidelines in a 10-year depression cohort of adult primary care patients

Abstract: Objective To describe the usage patterns of antidepressants with published CYP2D6- and CYP2C19-based prescribing guidelines among depressed primary care patients and estimate the proportion of patients taking antidepressants not recommended for them based on their CYP2C19 and CYP2D6 genotype-predicted metabolizer status. Methods Medication use and pharmacogenetic testing results were collected on 128 primary care patients enrolled in a 10-year depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A systematic review and meta-analysis [ 5 ] showed that CYP2C19 PMs had higher sertraline plasma concentrations, while Poweleit et al [ 18 ] showed that CYP2C19 status from PM to UM was inversely associated with sertraline doses at the beginning of treatment but not with doses in association with response. Overall, Jessel et al [ 19 ] found that 10% of individuals tended to switch if they were using antidepressants that were not in line with their CYP2C19 and/or CYP2D6 status, compared with 6% of patients who were using antidepressants that were aligned with their metabolizer phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis [ 5 ] showed that CYP2C19 PMs had higher sertraline plasma concentrations, while Poweleit et al [ 18 ] showed that CYP2C19 status from PM to UM was inversely associated with sertraline doses at the beginning of treatment but not with doses in association with response. Overall, Jessel et al [ 19 ] found that 10% of individuals tended to switch if they were using antidepressants that were not in line with their CYP2C19 and/or CYP2D6 status, compared with 6% of patients who were using antidepressants that were aligned with their metabolizer phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The discovered properties of the JNK inhibitor can be used to develop a fundamentally new approach to personification and increase the effectiveness of venlafaxine antidepressant therapy [7,8]. Based on the identified phenomena, JNK inactivation in liver cells can increase the level of drug transformation in low metabolizers (persons with low CYP2D6 expression, or in patients with liver diseases [3,4,6]) to the normal level (i.e. in extensive metabolizers of venlafaxine).…”
Section: Resultsmentioning
confidence: 99%
“…High incidence of depressive disorders in the population determines the widespread use in the medical practice of antidepressants, including venlafaxine [2,3]. This psychotropic pharmaceutical (presented by a racemate of R-and S-enantiomers) is one of the most effective modern antidepressants; its therapeutic effect is realized via blockade of serotonin, norepinephrine, and dopamine reuptake [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] The annual proportion of patients taking an antidepressant with published CYP2D6-or CYP2C19-based pharmacogenetic guidelines is high, ranging from 45% to 84%, in the adult primary care setting. 13 In some clinical studies, the use of pharmacogenetic-guided treatment in depression has been associated with increased treatment efficacy (i.e., symptom remission and treatment response) and increased medication tolerability. [14][15][16][17][18][19][20] However, other findings are inconsistent, with some trials not finding sustained responses or significant improvements in primary outcomes.…”
Section: Introductionmentioning
confidence: 99%